The selection of social networking sites using fuzzy analytical hierarchy process / Nor Nazuin Nazarail and Zurina Kasim - Nazarail, Nor Nazuin; Kasim, Zurina (Universiti Teknologi MARA Cawangan Pulau Pinang, 2021)
Social networks have penetrated internet users of all ages and become an important means of communication and entertainment, including in the student community. As the number of social networking sites grows, the selection of networking sites including Twitter, Facebook, Google+, Instagram and so on, is becoming increasingly critical for website operators, advertisers and even university students. This platform is becoming essential for business performance in dealing with modern generations to increase revenues and profits. Moreover, as the number of social networks increases, the user's tendency to make a choice is difficult. The market for social networking sites is highly competitive and changes in line with the trend. The objective of the research is to rank the most popular social networking sites Facebook, Instagram and Twitter among university students based on certain criteria. Therefore, this study proposes a solution by developing a mathematical technique which is the Fuzzy Analytical Hierarchy Process (FAHP) to estimate the relative importance of site criteria used in deciding the social site. The result of this study shows that Instagram has the first ranking followed by Facebook and Twitter. Functionality is the important criteria chosen with Renenue-generating opportunities as the preferred subcriteria. Content is the second criteria concerned followed by Usability and Privacy.